Pengaruh PAD, DAU, DAK, Dan DBH Terhadap Indeks Pembangunan Manusia (IPM) - Verra Rosyallia Widia Sofyan (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2023)
This study aims determine and analyze the effect of regional original income, general allocation funds, special allocation funds, and result share funds on human development index (HDI). The companies as for the samples, regencies and cities in West Java Province have budget realization reports every year for the 2014-2020 period and meet the requirements to be a sample of 23 consisting of regencies and 8 cities in West Java Province. The analytical method used is panel data regression. The sampling technique was carried out by purposive sampling method. The results of the study show that simultaneously local revenue, general allocation funds, special allocation fund and profit sharing funds have a significant effect on the human development index. While partially local revenue ha significant effect on the human development index, general allocation funds have significant effect on the human development index, special allocation funds have a significant effect on the human development index and profit sharing fund have a negative effect on the human development index. Key words: PAD,DAU,DAK,DBH